Adverse Childhood Experiences: Beyond Signs of Safety; Reimagining the Organisation and Practice of Social Work with Children and Families. (8th March 2019) - Spratt, Trevor; Devaney, John; Frederick, John
Abstract: While an adverse childhood experience (ACE)-informed approach to child protection and welfare has become influential in USA, it has had markedly less influence in UK, this despite growth in adoption of ACE research as a basis for understanding population needs and aligning service delivery amongst policymakers and other professional groups. In this article, we note the development of ACE research and draw out implications for social work with children and families. We argue that current organisational and practice preoccupations, drawing on the example of the Signs of Safety programme, together with antipathy to ACEs in some quarters of the social work academy, have the effect of reifying a short-term and occluded view of the developing child's needs so as to obstruct the systemic analysis and changes necessary to ensure that the child welfare system is redesigned to meet such needs. This suggests that post-Kempe era child welfare services are no longer conceptually or systemically adequate to protect children beyond immediate safety outcomes and consequently we need to reimagine their future.